2022
DOI: 10.3390/su14042352
|View full text |Cite
|
Sign up to set email alerts
|

A Circularity Evaluation of New Feed Categories in The Netherlands—Squaring the Circle: A Review

Abstract: The concept of circularity is currently proposed to address key sustainability issues affecting and affected by livestock production. Through a desk study, this paper evaluates some feed sources that are being developed in The Netherlands as an alternative to current feeds, namely food waste; seaweed; and localized production and alternative plant-based feed sources. These feed categories are evaluated according to four circularity criteria. The first two criteria concern standard circularity principles aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Adequate treatment of FW and sufficient quality control, regulation and management are of utmost importance [ 48 ]. The cattle mouth and foot disease outbreak that took place in the UK in 2001 and resulted in losses of up to 8 billion pounds [ 106 , 117 ] is a salient case. An investigation indicated that the origin of this outbreak was in a pig abattoir in Essex in February of the same year, 1 which was licensed to feed processed FW under the Animal Byproducts legislation of 1999 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate treatment of FW and sufficient quality control, regulation and management are of utmost importance [ 48 ]. The cattle mouth and foot disease outbreak that took place in the UK in 2001 and resulted in losses of up to 8 billion pounds [ 106 , 117 ] is a salient case. An investigation indicated that the origin of this outbreak was in a pig abattoir in Essex in February of the same year, 1 which was licensed to feed processed FW under the Animal Byproducts legislation of 1999 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accompanied by FW reduction, this allows for better alignment to CE framework objectives [ 113 , 136 ]. Hence, circularity concepts and improved methods of feed production from FW are encouraged in recent research studies without compromising health and safety [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they also argue that livestock breeding and feeding practices ought to orient itself towards efficiently and exclusively converting humanly non-edible biomass, in particular, of those locally available (ibid. ; see also Puente-Rodríguez et al, 2022).…”
Section: Global Oriented Agriculturementioning
confidence: 95%
“…There are also fatty acids that are free (12–14%) and have a C24–C32 chain length. Linear wax monoesters and hydroxymonoesters generated predominantly from myeloid, 15-hydroxypalmitic, and oleic acids have been found to consist of 35% to 45% hydroxymonoesters and linear wax monoesters, with chain lengths ranging from C40 to C48 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%